Dispersive Liquid-Liquid Microextraction of Cr(VI) in Water and Hair Samples by Electrothermal Atomic Absorption Spectrometry - Saber Tehrani, Mohammad; Abroum, Parviz; Waqif Husain, Syed; Shafaei, Faezeh (Asian Journal of Chemistry, 2010)
In this study, a dispersive liquid-liquid microextraction technique was combined with electrothermal atomic absorption spectrometry for preconcentration and determination of Cr(VI) in water and hair samples. Ammonium pyrrolidine dithiocarbamate, carbon tetrachloride and methanol were used as chelating agent, extraction and disperser solvent, respectively. Some variables influencing the microextraction and complex formation, including extraction and disperser type and volume, pH of the sample solution, extraction time, salt effect and amount of chelating agent were investigated. Under optimized conditions, the enrichment factor of 171 with a sample volume 5 mL was achieved. The detection limit for Cr(VI) was 5.96 ng L-1 and the relative standard deviation was 3.02 % (n = 10, c = 20 ng L-1). The method was successfully applied to the extraction and determination of Cr(VI) in several natural water and hair samples.